The South African economy macroeconomic prospects for the medium term - Tarp, Finn 1951-; Brixen, Peter (Routledge, 1996)
Although the scenarios produced may seem specific to South Africa, the methodology outlined is just as applicable to the policy-making process elsewhere. The IMF's Financial Programming and the World Bank's Revised Minimum Standard Model were central to many macroeconomic management studies of the 1980s, which focused on stabilization and structural adjustment. This study shows for the first time how they can be quantitatively applied and illustrates their strengths and weaknesses
Keywords: Geschichte 1991-1996; Econometrische modellen; Economische politiek; Macro-economie; Prévisions économiques - Afrique du Sud - Modèles économétriques; Wirtschaft; Wirtschaftspolitik; Ökonometrisches Modell; Economic forecasting -- South Africa -- Econometric models; Wirtschaftsentwicklung; Afrique du Sud - Conditions économques - 1991 - Modèles économétriques; Afrique du Sud - Politique économique - Modèles économétriques; Südafrika (Staat); South Africa -- Economic conditions -- 1991- -- Econometric models; South Africa -- Economic policy -- Econometric models; Südafrika